Perceived benefits and negative consequences of alcohol consumption in women living with HIV: a qualitative study - Robert L. Cook; Christa L. Cook; Manju Karki; Kathleen M. Weber; Kathleen A. Thoma; Chelsea M. Loy; Lakshmi Goparaju; Bridgett Rahim-Williams (BMC, 2016)
Abstract Background Women living with HIV have increased prevalence of medical and psychological comorbidities that could be adversely affected by alcohol consumption. Little is known about their unique motivations for drinking or perceptions of HIV-related consequences. In preparation for an alcohol intervention study, we sought to better understand reasons for drinking and perceived consequences of alcohol consumption among a sample of women living with HIV. Methods Four focus groups, with a total of 24 adult women (96 % African-American, 88 % HIV-positive), were conducted in Jacksonville, FL, Washington, DC and Chicago, IL. Focus group discussions were tape-recorded and transcribed verbatim; a conventional content analysis approach was used to identify themes, that were then grouped according to a biopsychosocial model. Results Regarding reasons for drinking, women described themes that included biological (addiction, to manage pain), psychological (coping, to escape bad experiences, to feel in control), and social (peer pressure, family). Themes related to consequences from alcohol included biological (damage to body, poor adherence to medications), psychological (risky or regrettable behavior, memory loss), and social (jail, loss of respect, poor choices). When discussing how their drinking impacted their health, women focused on broader issues, rather than HIV-specific issues. Conclusion Many women living with HIV are drinking alcohol in order to self-manage pain or emotions, and their perceived consequences from drinking extend beyond HIV-specific medical issues. Most participants described themes related to psychological issues and situations that are common in women living with HIV. Interventions to address drinking should inquire more specifically about drinking to manage pain or emotion, and help women to recognize the potential adverse impact of alcohol on comorbid health issues, including their own HIV infection.